Matchmaking facilitates the diagnosis of an autosomal‐recessive mitochondrial disease caused by biallelic mutation of the tRNA isopentenyltransferase (TRIT1) gene. Issue 5 (6th March 2017) - Kernohan, Kristin D.; Dyment, David A.; Pupavac, Mihaela; Cramer, Zvi; McBride, Arran; Bernard, Genevieve; Straub, Isabella; Tetreault, Martine; Hartley, Taila; Huang, Lijia; Sell, Erick; Majewski, Jacek; et al.
Abstract : Four individuals from three unrelated families with developmental delay, epilepsy, and microcephaly underwent exome sequencing which identified biallelic TRIT1 mutations as the most likely cause of their condition. TRIT1 was then entered into matchmaking programs by the identifying groups, which led to confirmation of this gene‐disease association and facilitated cellular phenotyping studies Abstract: Deleterious variants in the same gene present in two or more families with overlapping clinical features provide convincing evidence of a disease–gene association; this can be a challenge in the study of ultrarare diseases. To facilitate the identification of additional families, several groups have created "matching" platforms. We describe four individuals from three unrelated families "matched" by GeneMatcher and MatchMakerExchange. Individuals had microcephaly, developmental delay, epilepsy, and recessive mutations in TRIT1 . A single homozygous mutation in TRIT1 associated with similar features had previously been reported in one family. The identification of these individuals provides additional evidence to support TRIT1 as the disease‐causing gene and interprets the variants as "pathogenic." TRIT1 functions to modify mitochondrial tRNAs and is necessary for protein translation. We show that dysfunctional TRIT1 results in decreased levels of select mitochondrial proteins. Our findings confirm the TRIT1 disease association and advance the phenotypic and molecular understanding of this disorder.